Emergency Government of The Republic of Indonesia: Status Quo in State of Emergency - Irfan Zidni; Qurrata Ayuni (Fakultas Syariah UIN Sultan Maulana Hasanuddin Banten, 2022)
There is a constitutional status quo regarding the urgency of establishing the Emergency Government of the Republic of Indonesia or Pemerintah Darurat Republik Indonesia (PDRI). The military aggression was carried out by the Dutch who had seized Yogyakarta's position as the State Capital and kidnapped President Soekarno, and Vice President Moh. Hatta and several ministers put the position and sustainability of the Indonesian state at stake. This paper discusses the urgency of the establishment of the PDRI and explores its constitutionality in a review of the state of emergency and the Triumvirate concept. Using the normative juridical historical research method, this paper discusses two findings: First, the formation of the Emergency Government of the Republic of Indonesia was motivated by the Dutch Military Aggression incident which occupied the State Capital of Yogyakarta and kidnapped the President, Vice President and several State Ministers resulting in a state crisis and a government vacuum. Second, the formation of PDRI using Law Number 6 of 1946 which contains Article 12 of the Constitution is included in the emergency legal regime. The appointment of Mr Sjafruddin Prawiranegara who at that time was the Minister of Prosperity received a direct mandate from President Soekarno to form the PDRI based on a telegram dated December 19, 1948. Although the mechanism for establishing an emergency government in the form of a triumvirate has not been regulated in the constitution, this is not a constitutional deviation as is known in the state of emergency doctrine.